Dynamicity in Host Metabolic Adaptation Is Influenced by the Synergistic Effect of Eugenol Oleate and Amphotericin B During Leishmania donovani Infection In Vitro - Kar, Amrita; Jayaraman, Adithyan; Kumar, Avanthika; Kar Mahapatra, Santanu (Frontiers in Cellular and Infection Microbiology, 2021)
Immune metabolic adaptation in macrophages by intracellular parasites is recognized to recreate a crucial role during Leishmania infection. Nonetheless, small information is accessible regarding changes in a metabolic switch in L. donovani infected macrophages. Earlier we have reported the anti-leishmanial synergic effect of eugenol oleate with amphotericin B. Herein, we demonstrated that glycolytic enzymes were highly expressed in infected macrophages during combinatorial treatment of eugenol oleate (2.5 µM) and amphotericin B (0.3125 µM). Additionally, we found the biphasic role in arachidonic acid metabolite, PGE2, and LTB4, release during this treatment. In vitro data showed that COX-2 mediated PGE2 synthesis increased significantly (p<0.01) in infected macrophages. Not only that the level of prostaglandin synthesis was decreased 4.38 folds in infected macrophages after treatment with eugenol oleate with amphotericin B. Besides that, the mRNA expression of PTGES, MPGES, PTGER4 were moderately expressed in infected macrophages, while found decreased in combinatorial treatment. In addition, NOS2 expression was activated by the phosphorylation of p38MAPK during combination-treated macrophages promoted to intracellular parasite killing. Collectively, our findings in the present study indicated that the synergism between eugenol oleate and amphotericin B could play an important role in immune metabolism adaptation with a concomitant increase in host immune response against the intracellular pathogen, L. donovani.